The extent of cyclin D1 expression in endometrial pathologies and relevance of cyclin D1 with the clinicopathological features of endometrioid endometrial carcinoma - Hulya Tosun Yildirim; Dondu Nergiz; Canan Sadullahoglu; Zelal Akgunduz; Senay Yildirim; Selen Dogan; Cem Sezer (Wolters Kluwer Medknow Publications, 2020)
Background: Cyclin D1, a member of the cyclin protein family, is instrumental in the cell cycle due to its influence on the progression from G1 to the S phase. Its overexpression causes reduced doubling time and is also associated with clonogenic growth. The purpose of the present study was to assess cyclin D1 expression in patients with simple hyperplasia (SH), endometrial intraepithelial neoplasia (EIN) and endometrioid endometrial carcinoma, and to evaluate whether there was an association between cyclin D1 expression and the clinicopathological features of endometrioid endometrial carcinoma. Methods: Retrospective data were available for 193 patients (30 SH, 40 EIN, and 123 endometrioid endometrial carcinoma cases). To detect cyclin D1 expression, immunohistochemistry staining was performed with tissue microarrays. Results: The percentage of cases with positive cyclin D1 staining were 30%, 60% and 78%, for SH, EIN and endometrioid endometrial carcinoma, respectively (P < 0.001). Carcinomas with higher nuclear grade, histological grade, and FIGO grade displayed higher mean cyclin D1 expression compared to lower grade carcinomas. In addition, patients with lymphovascular invasion (P = 0.006), myometrial invasion (P < 0.001) and lymph node invasion (P < 0.001) had higher mean cyclin D1 expression compared to those without invasion. There was a significant correlation between cyclin D1 expression and clinicopathological features of endometrioid endometrial carcinoma including tumor grade, FIGO grade, lymphovascular invasion, lymph node invasion and myometrial invasion (P < 0.05 for each). Conclusion: Cyclin D1 expression is significantly higher in patients with endometrioid endometrial carcinoma compared to that of the SH and EIN. The extent of cyclin D1 expression is strongly correlated with nuclear and histological grade, myometrial invasion, lymphovascular invasion and lymph node invasion in patients with endometrioid endometrial carcinoma. These findings contribute in several ways to our understanding of cyclin D1 expression and provide a basis for future research on this topic.